2020
DOI: 10.1177/0300060520945140
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 tympanoplasty in patients with large perforations: Comparison of temporalis fascia, partial-thickness cartilage, and full-thickness cartilage

Abstract: Objective This study aimed to compare the results of different graft materials in type I tympanoplasty for patients with a large perforation of the tympanic membrane. Methods We performed a retrospective study on 180 patients with type I tympanoplasty. The patients were divided into three groups according to the repair materials used. Age, sex, pre- and postoperative hearing levels, mean air–bone gap, rate of graft success, hearing gain, and the postoperative graft failure rate were evaluated. We continued to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
2
7
0
3
Order By: Relevance
“…Our results can be supported by Xing et al, 2020 who reported that the success rate was 96.7% in the partialthickness cartilage and full-thickness cartilage groups, and >90% in the temporalis fascia group. There was no difference in the success rate among the groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results can be supported by Xing et al, 2020 who reported that the success rate was 96.7% in the partialthickness cartilage and full-thickness cartilage groups, and >90% in the temporalis fascia group. There was no difference in the success rate among the groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, the study by Xing et al, 2020 reported that the air conduction threshold was significantly higher before the operation than after the operation in the temporalis fascia, partial-thickness cartilage, and full-thickness cartilage groups. Although the hearing gain in the temporalis fascia group and the partialthickness cartilage group was higher than that in the full-thickness cartilage group, there was no significant difference in the graft success rate among the groups.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, hearing gain can be fewer in cartilage tympanoplasty than other graft materials unless cartilage has been thinned. Several previous studies have proven that partial‐thickness cartilage is better than full‐thickness cartilage for improvement of hearing 10,11 . Slicing the cartilage graft is the most commonly used method for thinning.…”
Section: Introductionmentioning
confidence: 99%
“…The full‐text review was performed on 709 studies, of which 624 were excluded for reasons such as failure to report TM perforation size, inability to stratify outcomes by perforation size, incorrect graft type, and no free full‐text. Following a thorough full‐text review, 85 studies were eventually selected for having met full inclusion criteria 10,14,15,17,18,25‐104 . A comprehensive overview of the search process is detailed in the corresponding PRISMA diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%